UNDERSTANDING INDONESIAN AND INTERNATIONAL MEDICAL STUDENT-PERCEIVED LANGUAGE NEEDS AND CHALLENGES: A CASE STUDY IN AN INDONESIAN UNIVERSITY - Beleven Khrismawan (Erudio Journal of Educational Innovation, 2019)
A well-established needs analysis is essential for a successful language program. This article reports the results of a questionnaire-based survey conducted to a sample of 44 Indonesian and 16 international students enrolled in an undergraduate medical school in an Indonesian university. The data were compared in terms of the mean, standard deviation and percentage. The results showed both groups perceived reading skills as their most important language skills to acquire, which was followed by speaking, listening and writing consecutively. The needs for improving reading skills were confirmed in the analysis of students’ areas of difficulties, where both groups were in consensus in perceiving reading medical English texts as the most challenging task.